PAJAK DIGITAL: POTENSI DAN TANTANGAN - Dwi Marlina Wijayanti (Universitas Ahmad Dahlan, 2020)
This study aims to analyze the potential and challenges of taxation in the digital era and Â understanding the readiness of business actors conducting business activities through E-commerce (PMSE) to the new taxation rules. In addition, this study also provides an overview of taxation policies that are appropriate to the digital era. There are still many potential taxation that has not been touched. One of the biggest potential is in digital companies. Tax regulations for digital companies are still under discussion by the government. But for business operators who carry out PMSE, there is a regulation which requires them to pay taxes. Observations indicate that the majority of business operators conducting PMSEs are not yet aware of the latest tax regulations. Literacy is needed so that more tax objects are aware on tax. Nevertheless, the results show that business operators are ready to be confirmed as taxpayers in accordance with applicable regulations. This is a big opportunity in the taxation sector.